The physics of foraging an introduction to random searches and biological encounters - Viswanathan, Gandhimohan M.; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"Do the movements of animals, including humans, follow patterns that can be described quantitatively by simple laws of motion? If so, then why? These questions have attracted the attention of scientists in many disciplines, and stimulated debates ranging from ecological matters to queries such as 'how can there be free will if one follows a law of motion?' This is the first book on this rapidly evolving subject, introducing random searches and foraging in a way that can be understood by readers without a previous background on the subject. It reviews theory as well as experiment, addresses open problems and perspectives, and discusses applications ranging from the colonization of Madagascar by Austronesians to the diffusion of genetically modified crops. The book will interest physicists working in the field of anomalous diffusion and movement ecology as well as ecologists already familiar with the concepts and methods of statistical physics"--
Machine generated contents note: Part I. Introduction: Movement: 1. Empirical motivation for studying movement; 2. Statistical physics of biological motion; 3. Random walks and Le;vy flights; 4. Wandering albatrosses; Part II. Experimental Findings: 5. Early studies; 6. Evidence of anomalous diffusion; 7. Human dispersal; 8. How strong is the evidence?; Part III. Theory of Foraging: 9. Optimizing encounter rates; 10. Le;vy flight foraging; 11. Other search models; Part IV. Finale: A Broader Context: 12. Superdiffusive random searches; 13. Adaptational versus emergent superdiffusion; 14. Perspectives and open problems; Appendices; References; Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Animal behavior -- Mathematical models; Home range (Animal geography) -- Mathematical models; Biological invasions -- Mathematical models; Animal ecology -- Mathematical models; Electronic books